Direito Brasileiro da concorrência e acesso à saúde no Brasil: Preços exploratórios no setor de medicamentos - Bruno Braz de Castro (South Centre, 2022)
– This paper aims to analyze the interfaces between Brazilian Competition Law and the issue of access to medicines, with special focus on abuses of industrial property rights in their exclusionary and exploitative effects. The paper analyzes the case law of the Brazilian Administrative Council for Economic Defense (CADE) in the medicines sector and discusses the abuses aiming at the illegitimate imposition of non-existent or invalid intellectual property rights with anticompetitive purposes. It then addresses the abuses in the exercise of industrial property rights that are, in themselves, valid: exclusionary practices aimed at artificially raising barriers to entry, and exploitative practices, directly translated into the exercise of market power to the detriment of the consumer. The latter are turned into exploitative excessive prices, contractual degradations, quality or privacy degradations, as well as restrictions on supply such as hoarding/impediment to the exploitation of industrial property rights. The paper concludes that the prohibition of exploitative pricing under the current competition law is legally valid and effective, with certain methodological concerns in order to minimize the risk of wrongful convictions (such as the construction of 'screening' tests of markets that are candidates for intervention). In view of such guidelines, the pharmaceutical industry appears to be an important candidate for antitrust attention, given the magnitude of the damages potentially derived from the non-intervention on the practice. Remedies in this area, importantly, should focus on identifying and solving the sector's structural competitive problems. In the case of drugs subject to price regulation by the Drugs Market Regulation Chamber (CMED), the technical expertise of the competition authority may be of great value in competition advocacy, which is demonstrated in light of the recent discussions about extraordinary price adjustments due to competitive problems in a given market.
Keywords: 300; Access to Healthcare; Access to Medicines; Antitrust; Brazil; Competition; Competition Law; Competition Policy; Competition Regulation; COVID-19; Health; Industrial Property; Industrial Property Rights; Intellectual Property; Intellectual Property Rights (IPRs); Pandemic; Pharmaceuticals